2014
DOI: 10.1128/aac.01087-13
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Application of Nonantifungal Drugs

Abstract: cCandida species are the cause of 60% of all mycoses in immunosuppressed individuals, leading to ϳ150,000 deaths annually due to systemic infections, whereas the current antifungal therapies either have toxic side effects or are insufficiently efficient. We performed a screening of two compound libraries, the Enzo and the Institute for Molecular Medicine Finland (FIMM) oncology collection library, for anti-Candida activity based on the European Committee on Antimicrobial Susceptibility Testing (EUCAST) guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 51 publications
1
50
0
2
Order By: Relevance
“…A previous report has suggested that C. albicans and C. glabrata have susceptibility to auranofin [35]. Notably, C. neoformans was inhibited at a low MIC that was reduced even further by oxide stressors.…”
Section: Discussionmentioning
confidence: 77%
“…A previous report has suggested that C. albicans and C. glabrata have susceptibility to auranofin [35]. Notably, C. neoformans was inhibited at a low MIC that was reduced even further by oxide stressors.…”
Section: Discussionmentioning
confidence: 77%
“…The fungicidal activity of CeO 2 NPs was found to be maximum in the case of Mucor species with ZOI of 22 mm, showing great competency as an antifungal agent, like other antifungal candidates. 41 The Figure 11 schematic illustration of ceO 2 NPs antibacterial activity. Abbreviations: NPs, nanoparticles; rOs, reactive oxygen species.…”
Section: Antifungal Assay Analysis Of Ceo 2 Npsmentioning
confidence: 99%
“…The various associations tested the most common are those where fluconazole is used as a prototype Stylianou et al, 2014). In our work we used a widely used antifungal miconazole and rarely described when evaluating synergy.…”
Section: Discussionmentioning
confidence: 99%